The McGraw-Hill Reader: Issues Across the Disciplines - H. Muller Gilbert (Mc Graw Hill, 2006)
I found this book very useful and with an excellent range of topics and readings. Used in WRC 1023 at UTSA. We did not read the entire book, but I found such interesting articles within the book that I ended up reading a large number of additional topics just out of curiousity. This book has a great section on "How to Mark a Book" and a very good section on "The Writing Process". Also includes some famous images from past newspaper articles and magazines